Implementasi Teknik Pengelolaan Diri Untuk Meningkatkan Kedisiplinan Siswa - Hasbahuddin hasbahuddin; Rosmawati Rosmawati (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2019)
The main problem that occurs in schools is the low application of learning discipline for students. Self-management is a procedure where the individual organizes himself in this technique the individual is involved in some or all of the basic components. The purpose of this study is to implement self-management techniques to improve student discipline in Pangkep Regency. This research design model is a one-group pretest-posttest design. The instrument used in this study was a student discipline questionnaire and self-management scenario implementation techniques. The sample in this study were 30 students. The data analysis technique used is descriptive statistics and inferential statistics using the t test as a hypothesis test. The results showed that the level of student discipline before being treated in the form of self-management techniques was in the low category. Furthermore, the level of student discipline after being given treatment in the form of self-management techniques is in the high category. In addition, based on the results of the research hypothesis test, it can be concluded that there is an influence of the implementation strategy of self-management techniques to improve student discipline in SMA 3 Pangkep, meaning that through the implementation of self-management techniques, student discipline will increase.